Kepemimpinan Kepala Sekolah dalam Meningkatkan Mutu Pendidikan Di SMK Aswaja Kecamatan Cluring - Syarifudin, Rahmat (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) STIB Banyuwangi, 2022)
This study aims to find and describe the leadership role of the principal of SMK Aswaja, Cluring District in improving the quality of education. The research method is qualitative, the type of research is eightfold. The method of obtaining data using interviews, observations, and documentation, data analysis using reduction, display, and conclution. Based on the results of the study, it can be concluded that the leadership role of the principal of SMK Aswaja, Cluring District, is at least two dominant ones, first as an educator and cultivating discipline and integrity. These two roles have tremendous implications for the progress of the SMK Aswaja institution, Cluring District, during his leadership. The changes in the students and teachers of SMK Aswaja, Cluring District, in leadership to the school appear to be of high quality and increase in quantity